TYPOLOGY OF FINANCIAL FRAUD IN UKRAINIAN COMMERCIAL BANKS - Мельник , Сергій (Socio-economic relations in the digital society, 2019)
The problem of the financial fraud in Ukrainian commercial banks and financial consequences it entails is reviewed in the article. The features of a financial fraud through its entity common for the banking sector of Ukraine are analysed. Subsequently the study presents a financial fraud typology with the following entities prevalent in Ukrainian commercial banks: financial fraud, which leads to loss of funds due to wealth extraction from the commercial bank and subsequently the latter going bankrupt; financial fraud, which leads to loss of funds due to unfair commercial bank borrower fraudulent procurement of finances and subsequently bank going bankrupt; financial fraud, which leads to loss of funds caused by a commercial bank lending finances to commercial bank owners and management affiliates; financial fraud, which leads to loss of funds due to a commercial bank loaning front parties or persons providing lost or falsified documents; financial fraud, which leads a commercial bank to loss of cash due to a fraudulent release of security interests, giving / receiving of false security interests; financial fraud, which leads commercial banks to loss of funds due to its deposition on correspondent accounts in foreign commercial banks of dubious reputation; financial fraud, which leads commercial banks to money loss due to the borrowers’ location or their property, security interests, surety, etc. being on the temporarily occupied territories and in the area of antiterrorist operation; financial fraud, which leads to a fraudulent acquisition of commercial bank customer funds and a commercial bank itself, as a result of the transfer to an affiliated non-bank financial institution; financial fraud, which leads to a fraudulent acquisition of commercial bank customer funds and a commercial bank itself, as a result of unauthorized interference with the banking software providing cash flow, ATM services etc.